Vegetation structural change since 1981 significantly enhanced the terrestrial carbon sink - Jing M. Chen (Nature Portfolio, 2019)
There lacks systematic analysis on the importance of vegetation structural change in the global terrestrial carbon cycle. Here the authors conducted a multi-model comparison analysis and find that the increase in leaf area index has been responsible for 12.4% of the accumulated terrestrial carbon sink from 1981 to 2016.